Liar & spy - Stead, Rebecca (Wendy Lamb Books, 2012)
Seventh-grader Georges adjusts to moving from a house to an apartment, his father's efforts to start a new business, his mother's extra shifts as a nurse, being picked on at school, and Safer, a boy who wants his help spying on another resident of their building.